Infant learning platform using Arduino - Low, Trudy Zhi Jia (Nanyang Technological University, 2020)
The Infant Learning Platform is inspired by the many toys in the market that aids the development of fine motor skills in infants. The targeted age range of infants is above 4 months of age, as infants below 4 months of age do not have hand muscles that are developed enough to utilise the platform. By refining their fine motor skills, infants will be impacted positively as they grow. This assists their physical, emotional and psychological development. Parents are able to make changes to the platform, according to the infant’s level of understanding. As the infant grows up, their intelligence increases, allowing them to explore the more difficult level of the platform. This allows the infant to continue learning as they grow, which corresponds to the name of the Infant Learning Platform.